Neuroprotective Effects of a PSD-95 Inhibitor in Neonatal Hypoxic-Ischemic Brain Injury - Baofeng Xu; Ai-Jiao Xiao; Wenliang Chen; Ekaterina Turlova; Rui Liu; Andrew Barszczyk; Christopher L. F. Sun; Ling Liu; Michael Tymianski; Zhong-Ping Feng; Hong-Shuo Sun (Molecular Neurobiology, 2016)

Efficacy of Bt maize producing the Cry1Ac protein against two important pests of corn in China - Hong-Xing Chen; Rui Yang; Wang Yang; Liu Zhang; Ibrahima Camara; Xue-Hui Dong; Yi -Qing Liu; Wang-Peng Shi (Environmental Science and Pollution Research, 2016)

Molecular detection and genome characterization of porcine circovirus type 2 in rats captured on commercial swine farms - Shao-Lun Zhai; Sheng-Nan Chen; Wei Liu; Xiao-Peng Li; Su-Fang Deng; Xiao-Hui Wen; Man-Lin Luo; Dian-Hong Lv; Wen-Kang Wei; Rui-Ai Chen (Archives of Virology, 2016)

Neprilysin Confers Genetic Susceptibility to Alzheimer’s Disease in Han Chinese - Hui-Zhen Wang; Rui Bi; Deng-Feng Zhang; Guo-Dong Li; Xiao-Hong Ma; Yiru Fang; Tao Li; Chen Zhang; Yong-Gang Yao (Molecular Neurobiology, 2016)

Transcriptome analysis reveals translational regulation in barley microspore-derived embryogenic callus under salt stress - Cheng-hong Liu; Rui-ju Lu; Gui-mei Guo; Ting He; Ying-bo Li; Hong-wei Xu; Run-hong Gao; Zhi-wei Chen; Jian-hua Huang (Plant Cell Reports, 2016)

Chryseobacterium chengduensis sp. nov. isolated from the air of captive giant panda enclosures in Chengdu, China - Cai-fang Wen; Li-xin Xi; Shan Zhao; Zhong-xiang Hao; Lu Luo; Hong Liao; Zhen-rong Chen; Rong She; Guo-quan Han; San-jie Cao; Rui Wu; Qi-gui Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2016)

Progression and inflammation of human myeloid leukemia induced by ambient PM2.5 exposure - Xiao-Ting Jin; Mei-Lan Chen; Rui-Jin Li; Quan An; Li Song; Yi Zhao; Hong Xiao; Long Cheng; Zhuo-Yu Li (Archives of Toxicology, 2016)

Magnetic effervescent tablet-assisted ionic liquid dispersive liquid–liquid microextraction of selenium for speciation in foods and beverages - Xiaojun Wang; Long Wu; Jiaqi Cao; Xincheng Hong; Rui Ye; Weiji Chen; Ting Yuan (Food Additives & Contaminants: Part A, 2016)

Emergence of reticuloendotheliosis virus in pigeons in Guangdong Province, Southern China - Shao-Lun Zhai; Sheng-Nan Chen; Tao Lin; Xiao-Hui Wen; Wen-Kang Wei; Dian-Hong Lv; Rui-Ai Chen (Archives of Virology, 2016)

Alterations and correlations of the gut microbiome, metabolism and immunity in patients with primary biliary cirrhosis - Long‐Xian Lv; Dai‐Qiong Fang; Ding Shi; De‐Ying Chen; Ren Yan; Yi‐Xin Zhu; Yan‐Fei Chen; Li Shao; Fei‐Fei Guo; Wen‐Rui Wu; Ang Li; Hai‐Yan Shi; et al. (Environmental Microbiology, 2016)
Summary We selected 42 early‐stage primary biliary cirrhosis (PBC) patients and 30 healthy controls (HC). Metagenomic sequencing of the 16S rRNA gene was used to characterize the fecal microbiome. UPLC‐MS/MS assaying of small molecules was used to characterize the metabolomes of the serum, urine and feces. Liquid chip assaying of serum cytokines was used to characterize the immune profiles. The gut of PBC patients were depleted of some potentially beneficial bacteria, such as Acidobacteria, Lachnobacterium sp., Bacteroides eggerthii and Ruminococcus bromii , but were enriched in some bacterial taxa containing opportunistic pathogens, such as γ‐Proteobacteria, Enterobacteriaceae, Neisseriaceae, Spirochaetaceae , Veillonella , Streptococcus , Klebsiella , Actinobacillus pleuropneumoniae , Anaeroglobus geminatus , Enterobacter asburiae , Haemophilus parainfluenzae , Megasphaera micronuciformis and Paraprevotella clara . Several altered gut bacterial taxa exhibited potential interactions with PBC through their associations with altered metabolism, immunity and liver function indicators, such as those of Klebsiella with IL‐2A and Neisseriaceae with urinary indoleacrylate. Many gut bacteria, such as some members of Bacteroides, were altered in their associations with the immunity and metabolism of PBC patients, although their relative abundances were unchanged. Consequently, the gut microbiome is altered and may be critical for the onset or development of PBC by interacting with metabolism and immunity.

Improvement of soybean transformation via Agrobacterium tumefaciens methods involving α-aminooxyacetic acid and sonication treatments enlightened by gene expression profile analysis - Yan-Min Zhang; Zi-Hui Liu; Rui-Juan Yang; Guo-Liang Li; Xiu-Lin Guo; Hua-Ning Zhang; Hong-Mei Zhang; Rui Di; Qing-Song Zhao; Meng-Chen Zhang (Plant Cell Reports, 2016)

Erratum to: First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2016)

Lysobacter chengduensis sp. nov. Isolated from the Air of Captive Ailuropoda melanoleuca Enclosures in Chengdu, China - Caifang Wen; Lixin Xi; Rong She; Shan Zhao; Zhongxiang Hao; Lu Luo; Hong Liao; Zhenrong Chen; Guoquan Han; Sanjie Cao; Rui Wu; Qigui Yan; et al. (Current Microbiology, 2016)